Role of T2-weighted and Diffusion-weighted Imaging in Cervical Malignancy in Developing Countries - Hari Soekersi; Ignatius Irawan Hidayat; Annisa Fitriani Zeindadinanda; Viola Stephanie Warokko (Universitas Islam Bandung, 2022)
Cervical cancer is the second most common gynecologic malignancy in Asia and is the leading cause of death in women in developing countries. The cervical cancer stage will significantly affect the prognosis and management. Based on the International Federation of Gynecology and Obstetrics (FIGO) 2018 classification of cervical cancer, magnetic resonance imaging (MRI) has a crucial role in determining cervical cancer staging. This study aimed to evaluate the role of T2-weighted imaging (T2WI) and diffusion-weighted imaging (DWI) sequences in assessing cervical carcinoma, with the pathological diagnosis being taken as the standard for cervical cancer diagnosis. This study was conducted on seven patients diagnosed with cervical cancer from pathological examination in January 2020 to March 2021 in the Department of Radiology Dr. Hasan Sadikin General Hospital Bandung. We detect the presence of locoregional lesions and extensions of cervical carcinoma using MRI with T2WI and DWI sequences in patients who have previously been diagnosed histopathologically. This study involved seven cervical cancer patients. Pelvic MRI with T2WI and DWI sequences was performed. The imaging results in these patients show that one patient has stage IB1 cervical cancer, four patients have stage IIB, one patient has stage IIIA, and one has stage IIIC1 cervical cancer. This study concluded that T2WI and DWI sequences in MRI are essential and sufficient for diagnosing cervical cancer.